1989
DOI: 10.3758/bf03329888
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of male and female performance on a tactuospatial maze

Abstract: Sex differences in performance of a tactuospatial finger-maze task were assessed in 28 male and 32 female right-handed college undergraduates. The subjects performed the task with their nondominant left hand, and were trained to one error-free trial within specified time limits. Cognitive tests were administered to assess vocabulary, word fluency, and spatial relations capabilities. The results failed to indicate any significant sex differences in performance on the tactuospatial maze in terms of mean errors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…With respect to gender effects, men and women performed our maze task at the same level, corroborating findings by Alvis et al (1989) and Parlow and Kinsbourne (1990). Because the number of left and right-handed women and men was not equally divided in each group, we were not able to test the effect of handedness as well.…”
Section: Effects Of Transfer Direction Handedness and Gendersupporting
confidence: 76%
See 1 more Smart Citation
“…With respect to gender effects, men and women performed our maze task at the same level, corroborating findings by Alvis et al (1989) and Parlow and Kinsbourne (1990). Because the number of left and right-handed women and men was not equally divided in each group, we were not able to test the effect of handedness as well.…”
Section: Effects Of Transfer Direction Handedness and Gendersupporting
confidence: 76%
“…Additionally, there are also studies that report intermanual symmetry, with transfer to the dominant hand being similar to transfer to the non-dominant hand (Piccirilli, Finali, & Sciarma, 1989;Mandal, Singh, Asthana, & Srivastava, 1992;Rand, Hikosaka, Miyachi, Lu, & Miyashita, 1998;Schulze, Lüders, & Jäncke, 2002). Intermanual transfer effects have also been found to be dependent on handedness (Stoddard & Vaid, 1996;Schmidt, Oliveira, Rocha, & Abreu-Villaca, 2000) and gender (Schmidt et al, 2000), although also for these effects studies have been reported that found no differences between right-and left-handed participants (Mandal et al, 1992;Yamauchi, Imanaka, Nakayama, & Nishizawa, 2004) or between males and females (Alvis, Ward, & Dodson, 1989;Parlow & Kinsbourne, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, women's greater overestimation of hill slants is eliminated under haptic conditions (Proffitt et al, 1995). Furthermore, it has been shown that, in a tactuospatial finger-maze task, women perform equally to (Alvis, Ward, & Dodson, 1989) or better than (Biersner, 1980) men, and that, in a kinesthetic acuity task, men outperform women only if visual cues are added (Livesey & Intili, 1996). Finally, studies on samples of sighted blindfolded and blind participants show no sex differences in way finding (Passini, Proulx, & Rainville, 1990) or mental rotation (Marmor & Zaback, 1976).…”
mentioning
confidence: 99%
“…For most of these differences, there is an advantage in favor of males. However, there is evidence in support of a lack of sex differences in non--visual tasks [2], [17], [18], [19]. One interpretation of these data would suggest that men might have an advantage with visuo--spatial tasks, rather than with spatial tasks per se.…”
Section: Discussionmentioning
confidence: 63%